National innovation systems: Can they be copied? - Urmas Varblane (OrdnungsPolitisches Portal (OPO), 2012)
This chapter discusses the application of the national system approach in the catching up economies. It criticizes the assumption that there exists an optimal one-sizefits-all national innovation system model. The example is the Estonia-Finland case, in which Finland's national innovation system is being applied to Estonia. We argue that innovation is path dependent and that factors such as distance from the current technological frontier (latecomer or frontrunner) and different national knowledge bases must be considered when developing a national innovation system for a specific country. The aim of the chapter is thus two-fold: 1) we are interested in how the concept of innovation is presented and reproduced within the national context and 2) exploring the adverse effects of (re)producing National Innovations Systems in an uncritical and unreflexive manner.
Keywords: 330; National Innovation System; Copy; Estonia